The elephant keeper : caring for orphaned elephants in Zambia - Ruurs, Margriet; Covo, Pedro, 1988- (Toronto, ON : Kids Can Press, 2017)
"In 14-year-old Aaron's village in Zambia, poaching for ivory is common practice, and elephants are feared because of the danger they pose to humans and the damage they often cause to crops so important to the villagers' livelihoods. But when Aaron encounters a newborn elephant in distress, his instinct is not to run away, but to jump to its rescue. This is the beginning of a beautiful bond of friendship and a meaningful vocation. This moving story, written by Margriet Ruurs and stunningly illustrated by Pedro Covo, is inspired by the true story of Aaron and Zambezi-a teenage Zambian boy and an orphaned baby elephant that was rescued from a swimming pool at a holiday lodge. Aaron had been a casual laborer, just trying to make enough money to support his family, but when gamekeepers noticed his natural ability to care for animals, he was offered a job as an elephant keeper at the Lilayi Elephant Nursery, where his still works to this day. Zambezi was only one month old when he was found nearly drowning in a holiday lodge swimming pool. His mother had been killed by poachers and he'd been separated from his herd. Severely dehydrated, he'd tried to drink from the pool and had fallen in. Now Zambezi is nearly 6 years old and is doing very well. This unique informational picture book for middle-graders includes three non-fiction spreads, which provide intervals in the story and opportunities for classroom discussions. These spreads feature photos as well as information about elephants, poaching and the amazing work that is done at an elephant orphanage. At the end of the book there are suggestions for ways readers can help the cause."--
Based on a true story.
Elementary Grade.
880-
Keywords: Elephants -- Juvenile fiction; Animal rescue -- Juvenile fiction; Poaching -- Juvenile fiction; Elephants -- Juvenile fiction; Animal rescue -- Juvenile fiction; Poaching -- Juvenile fiction; Elephants; Animal rescue; Poaching